Studi Literatur: Intensi Konsumsi Sugar-Sweetened Beverages Ditinjau dari Prediktor Theory of Planned Behavior - Aphrodita Cahya Buwana (Universitas Airlangga, 2023)
Indonesia has the third highest consumption of sugar-sweetened beverages in Southeast Asia, with 20.23 liters/person annually. In Indonesia, SSBs are consumed at least once a week by 62% of children, 72% of adolescents and 61% of adults. Sugar-sweetened beverages (SSB) is a type of beverage that contains caloric sweeteners, such as carbonated drinks (soda), energy drinks, sweet tea, sports drinks, and fruit-flavored drinks. Sugar-sweetened beverages are favored by many people due to several factors, such as economic factors, social factors, and psychological factors. Consumption of sugar-sweetened beverages (SSB) contains risk factors, both physically and psychologically. One of the models and theories of healthy behavior that can explain individual intentions on a behavior, especially in the context of this study, namely the consumption of sugar-sweetened beverages in young individuals is the Theory of Planned Behavior (TPB). Therefore, the author would like to conduct a narrative literature review before conducting further research.